Adolescent and Young Adult ME/CFS After Confirmed or Probable COVID-19 - Petracek, Lindsay S.; Suskauer, Stacy J.; Vickers, Rebecca F.; Patel, Neel R.; Violand, Richard L.; Swope, Renee L.; Rowe, Peter C. (Frontiers in Medicine, 2021)
Introduction Fatigue is a common acute symptom following SARS-CoV-2 infection (COVID-19). The presence of persistent fatigue and impaired daily physical and cognitive function has led to speculation that like SARS-CoV-1 infection, COVID-19 will be followed by myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS). Methods and Results We describe three adolescent and young adult patients who had confirmed or probable COVID-19 infections early on during the pandemic and were referred for evaluation to the Chronic Fatigue Clinic at the Johns Hopkins Children’s Center. All patients reported orthostatic intolerance symptoms within the first two weeks of illness, and ten-minute passive standing tests were consistent with postural tachycardia syndrome. After six months of illness, all three patients met criteria for ME/CFS. Clinical features of interest included strong histories of allergies in all three patients, two of whom had elevations in plasma histamine. Each demonstrated limitations in symptom-free range of motion of the limbs and spine and two presented with pathological Hoffman reflexes. These comorbid features have been reported in adolescents and young adults with ME/CFS. Conclusion ME/CFS can be triggered by COVID-19 in adolescents and young adults. Further work is needed to determine the pathogenesis of ME/CFS after COVID-19 and optimal methods of treating these patients. Our preliminary study calls attention to several comorbid features that deserve further attention as potential targets for intervention. These include neuromuscular limitations that could be treated with manual forms of therapy, orthostatic intolerance and POTS for which there are multiple medications and non-pharmacologic therapies, treatable allergic and mast cell phenomena, and neurologic abnormalities that may require specific treatment. Larger studies will need to ascertain the prevalence of these abnormalities.